THE NEED TO APPLY NEW METHODS OF PSYCHOPHYSIOLOGICAL RESEARCH IN AVIATION MEDICINE - Синеглазов, В. М.; Ударцева, Т. Є. (Proceedings of National Aviation University (archive), 2021)
The problem of the human factor in aviation and modern directions of aviation medicine are considered. In order to improve the methods of studying the psychophysiological state of aviation operators, a new method of studying higher nervous activity has been proposed.